2020
DOI: 10.3390/ijerph17207399
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Spanish Version of the Physical Appearance Comparison Scales

Abstract: Physical appearance comparison has been widely studied because of its strong relationship with body dissatisfaction and disordered eating. The main objective of this study was to validate the physical appearance comparison scales (PACS-Revised and PACS-3) in a sample of Spanish men and women and examine their psychometric properties. The sample consisted of 1151 participants (age M = 22.31, SD = 3.40). A unidimensional structure was corroborated in the PACS-R, and three factors in the PACS-3 (proximal, distal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 49 publications
(77 reference statements)
1
15
0
Order By: Relevance
“…This also implies that the instrument can be recommended for the purpose of conducting reasonably unbiased comparisons between the population groups under consideration in terms of self-reported levels of body, eating, and exercise comparison orientation. In this vein, the pattern of differences observed in body-related comparisons between the age and gender groups considered in the present study is consistent with prior research [ 10 , 12 , 24 ]. We refer to the fact that body-related comparison scores favored females and individuals in their young adulthood over males and adolescents, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This also implies that the instrument can be recommended for the purpose of conducting reasonably unbiased comparisons between the population groups under consideration in terms of self-reported levels of body, eating, and exercise comparison orientation. In this vein, the pattern of differences observed in body-related comparisons between the age and gender groups considered in the present study is consistent with prior research [ 10 , 12 , 24 ]. We refer to the fact that body-related comparison scores favored females and individuals in their young adulthood over males and adolescents, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In the event that evidence was obtained to support measurement invariance of the BEECOM scores across age and gender groups, a secondary goal of the present study was to examine gender and age differences in ED-related comparison orientation. It was hypothesized that, in line with previous research examining appearance-focused comparisons [ 10 , 12 , 24 ], small-to-intermediate-sized differences would be found in favor of groups consisting of females and younger adults.…”
Section: Introductionmentioning
confidence: 92%
“…It comprises 11 items organized in a single factor structure and rated on a 5‐point scale (0 = never , 4 = always ). The Spanish‐language version validated by Senín‐Calderón et al (2020) replicated the single factor structure and showed a strong positive correlation with a measure of EDs.…”
Section: Methodsmentioning
confidence: 86%
“…Instagram is a social media platform based on photos and videos with a higher percentage of use among young adults between 18 years and 34 years of age, as well as women [ 4 - 7 ]. The platform allows users to upload photos that emphasize their physical attractiveness, which prior to posting can be edited using filters that are provided by the application [ 4 ]. As a consequence, there is an impact on stereotypes, beauty standards, and body image, especially among Instagram’s youngest users, who are the most susceptible [ 8 ].…”
Section: Introductionmentioning
confidence: 99%